Role of orexin in modulating arousal, feeding, and motivation - Tsujino, Natsuko; Sakurai, Takeshi (Frontiers in Behavioral Neuroscience, 2013)
Orexin deficiency results in narcolepsy in humans, dogs, and rodents, suggesting that the orexin system is particularly important for maintenance of wakefulness. However, orexin neurons are ‘multi-tasking’ neurons that regulate sleep/wake states as well as feeding behavior, emotion, and reward processes. Orexin deficiency causes abnormalities in energy homeostasis, stress-related behavior, and reward systems. Orexin excites waking-active monoaminergic and cholinergic neurons in the hypothalamus and brain stem regions to maintain a long, consolidated waking period. Orexin neurons also have reciprocal links with the hypothalamic nucleus, which regulates feeding. Moreover, the responsiveness of orexin neurons to peripheral metabolic cues suggests that these neurons have an important role as a link between energy homeostasis and vigilance states. The link between orexin and the ventral tegmental nucleus serves to motivate an animal to engage in goal-directed behavior. This review focuses on the interaction of orexin neurons with emotion, reward, and energy homeostasis systems. These connectivities are likely to be highly important to maintain proper vigilance states.